Greenhouse gas mitigation in agriculture - Smith, Pete; Martino, Daniel; Cai, Zucong; Gwary, Daniel; Janzen, Henry; Kumar, Pushpam; McCarl, Bruce; Ogle, Stephen; O'Mara, Frank; Rice, Charles; Scholes, Bob; Sirotenko, Oleg; et al. (Philosophical transactions of the Royal Society of London. Series B. Biological sciences, 2008)
Agricultural lands occupy 37% of the earth's land surface. Agriculture accounts for 52 and 84% of global anthropogenic methane and nitrous oxide emissions. Agricultural soils may also act as a sink or source for CO2, but the net flux is small. Many agricultural practices can potentially mitigate greenhouse gas (GHG) emissions, the most prominent of which are improved cropland and grazing land management and restoration of degraded lands and cultivated organic soils. Lower, but still significant mitigation potential is provided by water and rice management, set-aside, land use change and agroforestry, livestock management and manure management. The global technical mitigation potential from agriculture (excluding fossil fuel offsets from biomass) by 2030, considering all gases, is estimated to be approximately 5500-6000 Mt CO2-eq. yr−1, with economic potentials of approximately 1500-1600, 2500-2700 and 4000-4300 Mt CO2-eq. yr−1 at carbon prices of up to 20, up to 50 and up to 100 US$ t CO2-eq.−1, respectively. In addition, GHG emissions could be reduced by substitution of fossil fuels for energy production by agricultural feedstocks (e.g. crop residues, dung and dedicated energy crops). The economic mitigation potential of biomass energy from agriculture is estimated to be 640, 2240 and 16 000 Mt CO2-eq. yr−1 at 0-20, 0-50 and 0-100 US$ t CO2-eq.−1, respectively.